Implementasi Media Pembelajaran Audio Visual Sebagai Upaya Menarik Minat Belajar Siswa PAI dalam Pembelajaran Daring di SMPN 1 Lembeyan - Pariera Dinar Halizah; Zamzam Mustofa; Amir Mukminin (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2023)
Covid-19 disease has bad impact on education in Indonesia, and to replace all forms of education today. The government must make every attempts to stop the spread of the Covid-19. There has been a decline through online schools that require education in Indonesia. Apart from the current illness, students need to adopt new educational patterns. This online learning has an impact on teachers and students where teachers must optimize to be effective in online learning by mastering technology that is increasingly trending. Students are also bored with the monotony of online learning which tends to be less effective, students are not interested in learning. This study seeks to attract students interested in learning online through audio and video ads. This study was used to determine qualitative analysis using descriptive methods, interpreting texts from sources and types of methodologies, i.e. parables, lessons learned from SMPN 1 Lembeyan for Covid- 19. Display of information in this study is based on documentation, observations, interviews and analysis data in a presentation and presentation of common data. The result is that by using effective audio and video ads, students may experience learning difficulties or problems that lead to a decrease in their interest in learning while studying online at COVID- 19 and the spread of infectious diseases.